Improving the assessment of transferable skills in chemistry through evaluation of current practice - Southam, Daniel; Schultz, Madeleine; O'Brien, Glennys; Schmid, Siegbert; Lawrie, Gwendolyn; Priest, Samuel; Lim, Kieran; Pyke, Simon; Bedford, Simon; Jamie, Ian (Springer, 2019)
The development and assessment of transferable skills acquired by students, such as communication and teamwork, within undergraduate degrees is being increas-ingly emphasised. Many instructors have designed and implemented assessment tasks with the aim to provide students with opportunities to acquire and demon-strate these skills. We have now applied our previously published tool to evaluate whether assessment tasks allow students to demonstrate achievement of these transferable skills. The tool allows detailed evaluation of the alignment of any as-sessment item against the claimed set of learning outcomes. We present here two examples in which use of the tool provides evidence for the level of achievement of transferable skills and a further example of use of the tool to inform curricu-lum design and pedagogy, with the goal of increasing achievement of communi-cation and teamwork bench marks. Implications for practice in assessment design for learning are presented.